2019
DOI: 10.1590/1984-0462/;2019;37;4;00016
|View full text |Cite|
|
Sign up to set email alerts
|

Body Mass Index and Albumin Levels Are Associated With Pulmonary Function Parameters in Pediatric Subjects With Cystic Fibrosis

Abstract: Objective: To evaluate the association of body mass index (BMI) and albumin with pulmonary function in cystic fibrosis (CF) pediatric subjects.Methods: This is a cross-sectional study with clinically stable CF’s subjects. Clinical (pulmonary function) and nutritional evaluation (body mass index and albumin) were performed. Univariate analysis was performed using simple linear correlations. Regression analysis was performed using an exit level of p<0.05.Results: Seventy-eight CF’s subjects (mean age 12.8±3.8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…A study of African Americans with no cardiopulmonary or chest wall disease showed that BMI was negatively correlated with DLCO 21 . Another study on patients with COPD from China showed that BMI was positively correlated with DLCO and DLCO/VA 22 .A series of clinical studies on IPF showed that lower BMI is associated with a poorer outcome of IPF 23 25 , but indexes of pulmonary diffusion function were not observed in these studies. We speculate that better nutritional status may promote the recovery of lung injury from severe COVID-19, as BMI can be considered as an indicator of nutrition.…”
Section: Discussionmentioning
confidence: 96%
“…A study of African Americans with no cardiopulmonary or chest wall disease showed that BMI was negatively correlated with DLCO 21 . Another study on patients with COPD from China showed that BMI was positively correlated with DLCO and DLCO/VA 22 .A series of clinical studies on IPF showed that lower BMI is associated with a poorer outcome of IPF 23 25 , but indexes of pulmonary diffusion function were not observed in these studies. We speculate that better nutritional status may promote the recovery of lung injury from severe COVID-19, as BMI can be considered as an indicator of nutrition.…”
Section: Discussionmentioning
confidence: 96%
“…Poor nutritional status and reduced BMI are associated with lower lung function and increased mortality in CF [ 9 , 14 , 16 ], and therefore undoubtedly contribute to the sex disparity in CF survival. Furthermore, CF women have been found to have poorer medication and nutritional adherence, which may also contribute to reduced lung function [ 17 , 18 ] and worse health outcomes [ 19 ].…”
Section: The “Gender Gap” In Cf Survival and Pulmonary Outcomesmentioning
confidence: 99%
“…The associations of albumin and BMI with PF have been addressed in several studies [13]. For example, BMI and albumin have been reported to be independently associated with the predicted FEV1% in children with cystic brosis [13]. In addition, a correlation between FEV1 and BMI has been found by Popova et al in patients treated for pulmonary TB, with a level of 0.14 (P < 0.05) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, impairment of PF may then occur due to reduced physical activity (muscle atrophy) [11,12]. The associations of albumin and BMI with PF have been addressed in several studies [13]. For example, BMI and albumin have been reported to be independently associated with the predicted FEV1% in children with cystic brosis [13].…”
Section: Discussionmentioning
confidence: 99%